Implementasi Pendaftaran Tanah Sistematis Lengkap Berbasis Partisipasi Masyarakat di Desa Dukuh Kecamatan Ngadiluwih Kabupaten Kediri - Firdausi, Rohmatina (Jurnal Ilmiah Administrasi Publik, 2021)
Regulation of the Minister of Agrarian and Spatial Planning / Head of National Land Agency Number 6 of 2018 on 2018 on Complete Systematic Land Registration has been improved by adding its implementation based on society participation. This is to achieve the target in 2025 that all land must be registered. Kediri Regency in 2019 has 1.386 km² of land from 1.523.92 km² have not been certified. The head of the Kediri Regency Land Office formed 4 PTSL working area unit team but can not to handle the number of targets that had to be solved. Technical instructions of PTSL+PM is a reference to implement PTSL +PM in Dukuh Village so that the society can be actively helped Puldatan work quickly and carefully. The study aims to determine the implementation model of a complete systematic land registration policy based on society participatition in the Dukuh Village. The research method that will be used is a descriptive qualitative. Research has been taken and the resulths show that the implementation of the PTSL+PM policy in Dukuh Village has done well and achieve the registration target of 85% of the total quota of 2500 fields. This is seen from the content of the policy that requires the interests of the President in ensuring legal law. Adequate resource in terms od human resources, budget, facilities make implementation has done optimally in Dukuh Village.